Body Mass Index, Waist Circumference, and Cognitive Decline Among Chinese Older Adults: A Nationwide Retrospective Cohort Study - Liang, Fang; Fu, Jialin; Moore, Justin B.; Zhang, Xinge; Xu, Yijia; Qiu, Nan; Wang, Yechuang; Li, Rui (Frontiers in Aging Neuroscience, 2022)
Background The reported associations between body mass index (BMI), waist circumference (WC), and cognitive decline are not consistent, especially in older adults. Objective This study aims to investigate the longitudinal associations of BMI, WC, and their change values with cognitive decline among Chinese adults aged 60 years and older and to examine the potential moderating effect of sex on these relationships. Methods The participants in this study were from waves one to four (2011–2018) of the China Health and Retirement Longitudinal Study (CHARLS). Cognition function, BMI, and WC were measured at four examinations over 7 years. The interview-based cognitive assessments of memory, orientation and attention, and visuospatial ability were recorded. Standardized global cognitive scores were generated. BMI and WC were objectively measured. Mixed-effects models were performed to evaluate the associations. Results A final sample of 3,035 Chinese older adults [mean (SD) age, 66.94 (5.43) years; 40.16% (n = 1,219) women] were included. Higher BMI (estimate = 0.0107; SE = 0.0024; p < 0.0001) and WC (estimate = 0.0019; SE = 0.0006; p = 0.0037) were associated with slower cognition score decline over a 7-year follow-up, while greater BMI variability (estimate = −0.0365; SE = 0.0116; p = 0.0017) was related to faster cognition score decline. The results were not modified by sex. BMI-defined overweight (estimate = 0.0094; SE = 0.0043; p = 0.0298) was associated with a slower cognition score decline, and both large weight gain (estimate = −0.0266; SE = 0.0074; p = 0.0003) and large WC loss (estimate = −0.0668; SE = 0.0329; p = 0.0426) were associated with faster cognition score decline. Conclusion Among Chinese older adults, higher BMI, higher WC, and overweight are related to slower cognitive decline, while greater BMI variability, large weight gain, and large WC loss are associated with faster cognitive decline.